2018
DOI: 10.1093/ehjci/jex342
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing coronary artery disease after a positive coronary computed tomography angiography: the Dan-NICAD open label, parallel, head to head, randomized controlled diagnostic accuracy trial of cardiovascular magnetic resonance and myocardial perfusion scintigraphy

Abstract: Patients with low/intermediate CAD risk and a positive CCTA scan represent a challenge to perfusion techniques indicated by the low sensitivity of both CMR and MPS with FFR as a reference. The mechanisms underlying this discrepancy need further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 24 publications
0
53
0
1
Order By: Relevance
“…For CMR, an abnormal scan was defined as subendocardial or transmural changes by stress imaging or irreversible defects in ≥ 2 contiguous segments by late gadolinium enhancement imaging. Full description of MPS and CMR analysis was reported in the Dan-NICAD papers [14,15]. CMR core-lab readings were performed in an experienced core lab (William Harvey Research Institute, Queen Mary University of London, London, UK) while MPS Images were analyzed by a different independent core lab (Department of Nuclear Medicine, Aarhus University Hospital, Aarhus, Denmark).…”
Section: Non-invasive Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…For CMR, an abnormal scan was defined as subendocardial or transmural changes by stress imaging or irreversible defects in ≥ 2 contiguous segments by late gadolinium enhancement imaging. Full description of MPS and CMR analysis was reported in the Dan-NICAD papers [14,15]. CMR core-lab readings were performed in an experienced core lab (William Harvey Research Institute, Queen Mary University of London, London, UK) while MPS Images were analyzed by a different independent core lab (Department of Nuclear Medicine, Aarhus University Hospital, Aarhus, Denmark).…”
Section: Non-invasive Imagingmentioning
confidence: 99%
“…Remaining segments were defined as distal. We refer to the Dan-NICAD papers for further details [14,15].…”
Section: Invasive Coronary Angiography and Fractional Flow Reservementioning
confidence: 99%
“…In fact, only two-thirds of the patients to whom revascularization was exposure. [25][26][27] FFRCT may provide advantages in each of these areas, because of its accuracy 6-8 and elimination of additional visits and radiation exposure. Our analysis demonstrated that the proportion of patients deemed to require additional testing in Japan, at nearly 45% following the initial assessment by cCTA, was reduced to nearly zero (0.02%) after FFRCT analysis.…”
Section: Ffrct Reduced Additional Testing and Stratified Patientsmentioning
confidence: 99%
“…Indeed, the three false-negative cases in predicting FFR less than or equal to 0.8 all involved patients who did not respond to adenosine. Together, both provide a clue to the low diagnostic value of uncorrected perfusion MRI for FFR-defined myocardial ischemia, as reported in a recent trial [25], and indicate that relative perfusion index is the parameter with the greatest ability to control the confounders and the discrepancies between perfusion MRI and FFR-defined ischemia [17].…”
Section: Discussionmentioning
confidence: 95%